Imitation from Camões on Cristaes da alma (1673), by Gerardo de Escobar - Silva, Isabel Scremin da (2024)
This article aims at investigating the presence of Camões at the end of the 17th century in Portugal, based on Cristaes da Alma (1673), written by Gerardo de Escobar, pen name of Antônio de Escobar (1618-1681). Escobar’s imitation from Camões can be especially observed three times on Cristaes: when a rhetorical persona praises the eyes of a beloved woman, (anti)emulating Petrarca; when the persona walks through a wood and makes reference to the Giant Adamastor; when Aônio sighs and amplifies a sonnet from Camões. It will be highlighted the differences and similarities between Escobar’s and Camões’ poetry, considering Camões a fundamental authority in loving poetry during the 17th century.